VD_FINDINFO Arrêt / 2011 / 355 vom 4. April 2011 - VD Tribunal cantonal (2011)
RELATIONS PERSONNELLES, FRAIS JUDICIAIRES, CURATELLE ÉDUCATIVE, SURVEILLANCEEN GÉNÉRAL, VISITE | 273 CC, 276 CC, 307 CC, 420 al. 2 CC, 489 CPC, 174 al. 2 CDPJ